Growth of coffee (Coffea arabica L.) during nursery’s stage in response to the salinity generated by fertilizers - Sadeghian Khalajabadi, Siavosh; Zapata H., Raúl Dario (Revista de Ciencias Agrícolas, 2014)
Soil salinity can negatively affect plant growth and even cause their death. This research aimed to determine the effect of the salinity generated by fertilizers on coffee (Coffea Arabica L.) growth during the nursery stage. Soil samples were collected at two Experimental Stations (ES) of Cenicafé (Naranjal in the department of Caldas and Timbío in the department of Cauca) and at a coffee farm in Jamundí (Valle del Cauca). For each soil, the response of coffee Caturra variety was evaluated through a complete random design and 27 treatments (factorial 33 ), resulting from three doses of calcium-Ca, magnesium-Mg, and potassium-K (0, 1, and 3 g dm-3of soil), using sulfates sources. The electrical conductivity (E.C.), as an indicator of salinity, increased in accordance with the applied doses, with higher values for Mg, followed by K and Ca. This result was primarily related to the salinity index of the fertilizers and their solubility. The differences in E.C. between localities (EE Naranjal>EE Timbío>FC Jamundí) were attributed to their humidity retention capacity. As salinity increased, plant weight decreased, until causing toxicity symptoms and subsequent death. The critical level of E.C., calculated for 90% of the relative growth, corresponded to an average of 1.1 dS m-1.